The Study of Relative Expression of Key Genes of Thymol Biosynthesis Pathway in Thymus vulgaris cv. 'Varico 3' under Cold Stress Using Real-Time PCR - Sh Habibi; A Qaderi; F Fatehi (Institue of Medicinal Plants, ACECR, 2017)
Background: Thyme (Thymus vulgaris L.) is a valuable medicinal plant which has many secondary metabolites such as thymol and carvacrol. Objective: This study was done to evaluation of cold stress effect on gene expression in thymol biosynthesis pathway including DXR، HMGR and TPS1. Methods: The effect of cold stress in the time period of 0, 3, 12, 24 and 48 hours on gene expression in thymol biosynthesis pathway including DXR, HMGR and TPS1 was evaluated by RT-PCR. This study was done on base of complete randomized design (CRD) in Institute of Medicinal Plants, ACECR, Karaj, Iran. Results: Results showed that the cold stress had significantly effect on expression of studied genes. The highest expression of HMGR gene was observed within 3 hours after cold treatment (1.57 times more than control treatment).  The expression of DXR and TPS1 genes were reduced in different periods of cold stress. Conclusion: In general, the genes expression of thymol and carvacrol biosynthesis pathway including DXR, HMGR and TPS1 were significantly changed by cold stress.